New species of the Pseudancistrus barbatus group (Siluriformes, Loricariidae) with comments on its biogeography and dispersal routes - Costa e Silva, Gabriel de Souza da [UNESP]; Roxo, Fabio Fernandes [UNESP]; Britzke, Ricardo [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publ, 2014)
A new species of Pseudancistrus is described from the Tapajos Basin, and assigned to the P. barbatus group by having hypertrophied odontodes along the snout and lacking evertible cheek plates. The new species is distinguished from other species in that group (P. barbatus, P. corantijniensis, P. depressus and P. nigrescens) by its pattern of spots, length and color of snout odontodes, greater head depth, cleithral width, anal-fin spine length, peduncle depth and internares width. Molecular phylogenetic results corroborate placement of the new species in the Pseudancistrus barbatus group which is otherwise distributed in the Xingu Basin and rivers draining the Guyana Shield into the Atlantic Ocean. Topology tests strongly reject alternative hypotheses supporting close relationships with Guyanancistrus, Lithoxancistrus or the species Pseudancistrus pectegenitor, P. sidereus and P. genisetiger. Additionally, we propose two hypotheses on the distribution of the new species in the rio Tapajos, a Brazilian Shield drainage. The first one proposes that ancestral stock of the P. barbatus group was widely distributed throughout rivers draining the Guyana and Brazilian shields, and the species P. zawadzkii and Pseudancistrus sp. L17 are in the limit of the distribution for the group in Tapajos and Xingu rivers. The second hypothesis proposes that ancestral stock of the P. barbatus group was restricted to Guyana Shield rivers, and that headwater capture events permitted several dispersal routs through Guyana and Amazon rivers, permitted that the ancestral lineages of Pseudancistrus sp. L17 and P. zawadzkii reached the rivers of Amazon basin.
Keywords: Ancistrini; freshwater; molecular phylogeny; F-reticulon 4; Brazilian Shield